Nature of Neurological Complications and Outcome After Surgery for Type A Aortic Dissection - Biancari, Fausto; Onorati, Francesco; Peterss, Sven; Buech, Joscha; Mariscalco, Giovanni; Lega, Javier Rodriguez; Pinto, Angel G; Fiore, Antonio; Perrotti, Andrea; Hérve, Amelié; Rukosujew, Andreas; Demal, Till; et al. (The American journal of cardiology, 2024)
Surgery for type A aortic dissection (TAAD) is frequently complicated by neurologic complications. The prognostic impact of neurologic complications of different nature has been investigated in this study. The subjects of this analysis were 3,902 patients who underwent surgery for acute TAAD from the multicenter European Registry of Type A Aortic Dissection (ERTAAD). During the index hospitalization, 722 patients (18.5%) experienced stroke/global brain ischemia. Ischemic stroke was detected in 539 patients (13.8%), hemorrhagic stroke in 76 patients (1.9%) and global brain ischemia in 177 patients (4.5%), with a few patients having had findings of more than 1 of these conditions. In-hospital mortality was increased significantly in patients with postoperative ischemic stroke (25.6%, adjusted odds ratio [OR] 2.422, 95% confidence interval [CI] 1.825 to 3.216), hemorrhagic stroke (48.7%, adjusted OR 4.641, 95% CI 2.524 to 8.533), and global brain ischemia (74.0%, adjusted OR 22.275, 95% CI 14.537 to 35.524) compared with patients without neurologic complications (13.5%). Similarly, patients who experienced ischemic stroke (46.3%, adjusted hazard ratio [HR] 1.719, 95% CI 1.434 to 2.059), hemorrhagic stroke (62.8%, adjusted HR 3.236, 95% CI 2.314 to 4.525), and global brain ischemia (83.9%, adjusted HR 12.777, 95% CI 10.325 to 15.810) had significantly higher 5-year mortality than patients without postoperative neurologic complications (27.5%). The negative prognostic effect of neurologic complications on survival vanished about 1 year after surgery. In conclusion, postoperative ischemic stroke, hemorrhagic stroke, and global cerebral ischemia increased early and midterm mortality after surgery for acute TAAD. The magnitude of risk of mortality increased with the severity of the neurologic complications, with postoperative hemorrhagic stroke and global brain ischemia being highly lethal complications.
Keywords: Female; hemoragická cévní mozková příhoda; Aortic Dissection; Hemorrhagic Stroke; Europe; ženské pohlaví; mortalita v nemocnicích; Registries; aneurysma hrudní aorty; stroke; lidé; Evropa; aortic dissection; pooperační komplikace; disekce aorty; míra přežití; ischemie mozku; prognóza; Aortic Aneurysm, Thoracic; Risk Factors; retrospektivní studie; global cerebral ischemia; Male; Postoperative Complications; ischemická cévní mozková příhoda; Aged; Ischemic Stroke; Brain Ischemia; type A aortic dissection; rizikové faktory; Prognosis; Survival Rate; Hospital Mortality; lidé středního věku; registrace; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Humans